Pemeriksaan Haemoglobin pada Ibu Hamil Desa Bangun Rejo Kecamatan Tanjung Morawa Kabupaten Deli Serdang Provinsi Sumatera Utara Tahun 2024 - Kismiasih Adethia; Retno Wahyuni; Sonia Novita Sari; Nur Azizah; Diah Pitaloka (Pusat Riset dan Inovasi Nasional, 2024)
Anemia is the most common nutritional problem in Indonesia and in the world. Anemia is a condition where red cells are insufficient to meet the body's physiological needs. Basically, anemia is a condition where there is a decrease in hemoglobin, hematocrit and erythrocyte count below normal values. The process of this activity starts from the preparation, implementation and evaluation stages. The result was that the participants were 23 pregnant mothers who lived in Bangun Rejo Village. During the implementation, the mothers' hemoglobin levels were checked after which they were given education about anemia in pregnancy. The conclusion of this service is that 19 pregnant women (82.6%) did not experience anemia and 4 people (17.4%) experienced mild anemia and after the examination, pregnant women were given education about anemia in pregnant women. It is hoped that pregnant women will pay more attention to the condition of their pregnancy and eat food that contains good nutrition for pregnant women and have their condition checked regularly.